Online Learning Versus Blended Learning: An Exploratory Study - Cross, Andrew; Ashok, B.; Bala, Srinath; Cutrell, Ed; Datha, Naren; Kumar, Rahul; Kumar, Viraj; Parthasarathy, Madhusudan; Prakash, Siddharth; Rajamani, Sriram; Sangameswaran, Satish; Sharma, Deepika; et al. (2014)
Due to the recent emergence of massive open online courses (MOOCs), students and teachers are gaining unprecedented access to high-quality educational content. However, many questions remain on how best to utilize that content in a classroom environment. In this small-scale, exploratory study, we compared two ways of using a recorded video lecture. In the online learning condition, students viewed the video on a personal computer, and also viewed a follow-up tutorial (a quiz review) on the computer. In the blended learning condition, students viewed the video as a group in a classroom, and received the follow-up tutorial from a live lecturer. We randomly assigned 102 students to these conditions, and assessed learning outcomes via a series of quizzes. While we saw significant learning gains after each session conducted, we did not observe any significant differences between the online and blended learning groups. We discuss these findings as well as areas for future work.